A Seat on the Aisle, Please! The Essential Guide to Urinary Tract Problems in Women - Kavaler, Elizabeth (Springer New York : Imprint: Copernicus, 2006)
In the course of a lifetime, more than half of all women will experience some form of debilitating pelvic disease or discomfort, including chronic urinary tract infections, various kinds of incontinence, pelvic floor prolapse, and interstitial cystitis. Surprisingly, until recently there has been only scant attention paid to this very common group of disorders, considering the vast population of sufferers. What's more, doctors have long tended to dismiss many symptoms of urinary tract disorders as an inevitable consequence of the aging process or, worse still, as indicators of underlying psychological disease. In this concise, clearly written, and sympathetic new book, Elizabeth Kavaler suggests that a new approach to UT disorders is long overdue. One of the surprisingly small number of female urologists practicing in the U.S., Dr. Kavaler explains what these diseases are and what patients can do to get themselves diagnosed and treated properly. But more than that, she extends an expert, sympathetic, and skilled hand to those who've been distressed, isolated, and embarrassed for too long.